2018
DOI: 10.1016/j.jid.2017.11.020
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Seborrheic Dermatitis: A Candidate Gene Approach and Pilot Genome-Wide Association Study

Abstract: Expanding the COL7A1 mutation database: novel and recurrent mutations and unusual genotype-phenotype constellations in 41 patients with dystrophic epidermolysis bullosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…A special feature of seborrhoeic dermatitis is that it can be triggered by stress factors, nutrition, drugs and skin irritations. Beyond such triggers, a genetic disposition has been discussed . It can impact the quality of life of those with the disease, which includes discomfort, stigmatization, loss of self‐esteem and limitations in social activities …”
mentioning
confidence: 99%
“…A special feature of seborrhoeic dermatitis is that it can be triggered by stress factors, nutrition, drugs and skin irritations. Beyond such triggers, a genetic disposition has been discussed . It can impact the quality of life of those with the disease, which includes discomfort, stigmatization, loss of self‐esteem and limitations in social activities …”
mentioning
confidence: 99%
“…PIRT is a modulator of TRPV1 (one of the regulators of itch) and TRPM8 (a regulator of epidermal homeostasis) (Bidaux et al, 2015;Patel et al, 2011;Tang et al, 2013). Therefore, this study showed that SD is probably associated with genetic susceptibility (Sanders et al, 2018b).…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 67%
“…e. Genome-wide association studies (GWASs) have not detected genome-wide significant associations for seborrheic dermatitis: Sanders et al (2018b) conducted a genome-wide association study that identified two genome-wide significant associations for SD. In this study, they included participants of the Rotterdam Study (Sanders et al, 2018a).…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%
See 2 more Smart Citations